Self-Care is Associated with Quality of Life in Chronic Kidney Disease Undergoing Hemodialysis Self-Care Dihubungkan dengan Kualitas Hidup pada Penyakit Ginjal Kronik yang Menjalani Hemodialisis - Rosyid, Fahrun Nur; Sugiharto, Sh; Dhani, Sheena Ramadhia Asmara; Vera, Lenia Septika; Safitri, Lisa Novia (Universitas Aisyah Pringsewu, 2025)
ABSTRACT Chronic Kidney Disease (CKD) significantly affects the quality of life of patients, often due to limitations in their ability to care for themselves. Effective self-care is crucial in managing CKD, as it directly affects daily routines and overall well-being. The aim of this study is to assess the relationship between self-care and the quality of life of CKD patients undergoing hemodialysis treatment. A quantitative, cross-sectional approach was used, involving 91 participants selected through accidental sampling. Data were collected using the